Preliminary phospholipase, Hemolytic and Bactericidal activity of the venom of the Snake of Cascabel Tolima - Solano Godoy, Jennifer Alexandra; Molano Cardona, Emerson David; Bernal Bautista, Manuel Hernando; Murillo Arango, Walter (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In the department of Tolima, there are no studies that allow us to specify with certainty the magnitude of the ophidic accident caused by Crotalus durissus; Therefore, there is a need to generate toxicological information, as well as knowledge of the potential antimicrobial potential of molecules such as proteins and peptides that make up the venom. In this work, we analyzed the electrophoretic profile by SDS-PAGE of crude venom extracted from individuals collected in the municipality of Natagaima (Tolima) and the association of its components with direct and indirect hemolytic activity on blood agar and its bactericidal activity. The potential of the crude venom against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeuroginosa was evaluated. The venom showed molecular weight bands 26.6 kDa., 17, 14.2, 6.5, 3.5 and 1.06 kDa., corresponding to reports of the venom of this species. The direct and indirect hemolytic activity was dose-dependent, with a minimum hemolytic dose of 200 mg / ml. The antimicrobial effect of the crude venom was differential on the microorganisms evaluated, presenting moderate activity on E. coli. The results constitute valuable data to preliminarily recognize the antimicrobial potential of Crotalus durissus venom (rattle) from the Natagaima-Tolima area.